Critical Terrorist Organizations and Terrorist Organization Alliance Networks Based on Key Nodes Founding - Hu, Jun; Chu, Chengbin; Xu, Ling; Wu, Peng; Lia, Hui-jia (Frontiers in Physics, 2021)
World peace is a prerequisite for the common development of all countries. Without a peaceful international environment and war,turmoil and conflict everywhere, the development of countries would be impossible. Therefore, only peace can ensure development. Today, people in many countries are still suffering from war and turmoil. According to the date of Global Terrorism Database. We find that there are many terrorist organizations make terrorist attacks together so to find the relationship is very important and finding the key organizations is also useful. Different key nodes finding-ways is useful, however they can only show the part information of the nodes, thus in this paper, we built a Terrorist Organization Alliance (TOA) Network and find a new way to analyze the key terrorist organizations in the TOA network. With the help of the entropy weight way, we find critical organizations is given base on these traditional methods and we use the $t$-test and convergence analysis to test the results, which find that the accuracy of our method is better than that of traditional methods.